2016
DOI: 10.2516/ogst/2016002
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Tungsten(VI) Penta-Methyl Complex: Synthesis, Characterization and its Application in Olefin Metathesis Reaction

Abstract: -Tungsten-hexa-methyl readily reacts with B(C 6 F 5 ) 3 in dichloromethane and generates the corresponding well-defined cationic tungsten-penta-methyl complex which was identified precisely by 1 H NMR, 13 C NMR, 1 H-13 C NMR correlation spectroscopy. Unlike WMe 6 , this cationic complex has low energy barrier to form tungsten carbene intermediate, which was further supported by the fact that WMe 6 alone has no activity in olefin metathesis reaction whereas the cationic complex shows catalytic activity for self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 23 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…14b We also found in the 1 H- 13 C correlation spectra that the peak at 0.5 ppm in the 1 H-NMR spectrum correlates with the peak at 10.8 ppm in the 13 C-NMR spectrum and the peak at 2.7 ppm in the 1 H-NMR spectrum correlates with the peak at 103.2 ppm in the 13 C-NMR spectrum. In separate experiments we synthesised 13 C labelled W(C 13 H 3 ) 6 and upon treatment with B(C 6 F 5 ) 3 in dichloromethane solution we have identified the incorporation of the labelled methyl into the [(C 13 H 3 )B(C 6 F 5 ) 3 ] À anion, in the final product. The above experiment clearly indicated that the methyl that bears [MeB(C 6 F 5 ) 3 ] À came from WMe 6 .…”
mentioning
confidence: 65%
See 4 more Smart Citations
“…14b We also found in the 1 H- 13 C correlation spectra that the peak at 0.5 ppm in the 1 H-NMR spectrum correlates with the peak at 10.8 ppm in the 13 C-NMR spectrum and the peak at 2.7 ppm in the 1 H-NMR spectrum correlates with the peak at 103.2 ppm in the 13 C-NMR spectrum. In separate experiments we synthesised 13 C labelled W(C 13 H 3 ) 6 and upon treatment with B(C 6 F 5 ) 3 in dichloromethane solution we have identified the incorporation of the labelled methyl into the [(C 13 H 3 )B(C 6 F 5 ) 3 ] À anion, in the final product. The above experiment clearly indicated that the methyl that bears [MeB(C 6 F 5 ) 3 ] À came from WMe 6 .…”
mentioning
confidence: 65%
“…1d) almost completely disappeared in less than 15 minutes with the formation of two new peaks at 2.7 and 0.48 ppm in the 1 H-NMR spectrum (Fig. 1a) and 103.2 and 10.8 ppm in the 13 C NMR spectrum (Fig. 1a and b).…”
mentioning
confidence: 96%
See 3 more Smart Citations